Impactos ambientales de la producción petrolera en Colombia y su relación con la innovación tecnológica en los últimos quince años (2020)
The environmental impacts Generated in oil production in Colombia are analyzed in this monograph for a solution for minimization. In this way, the present work provided an overview of the main impacts generated to the biotic, abiotic and socio-economic means during the oil exploitation, as well as the main activities to which they are attributed. Subsequently, the impacts were evaluated in a categorization form in the Super Decisions program with three proposed technologies. Consequently, a qualification of importance was obtained of both the impacts and the alternatives. In addition, an overview of the current situation of production water treatment in Colombia as a minimizer of the impact of production waters was reviewed, making an impact on the company Ecopetrol and its main advances in this area, and technologies that have yet to be implemented to minimize pollutants from various industrial wastewaters.